2019
DOI: 10.3847/1538-4357/ab40ca
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of Fragmentation, Substructure, and Protostars in High-mass Starless Clump Candidates

Abstract: The initial physical conditions of high-mass stars and protoclusters remain poorly characterized. To this end we present the first targeted ALMA Band 6 1.3 mm continuum and spectral line survey towards high-mass starless clump candidates, selecting a sample of 12 of the most massive candidates (4 × 10 2 M M cl 4 × 10 3 M ) within d < 5 kpc. The joint 12 + 7 m array maps have a high spatial resolution of 3000 au (0.015 pc, θ syn ≈ 0. 8) and have high point source mass-completeness down to M ≈ 0.3 M at 6σ rms (o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 114 publications
(164 reference statements)
12
74
0
Order By: Relevance
“…Also, when observed with ALMA at high-angular resolution, singledish starless sources observed in high-mass star-forming regions systematically fragment into a set of low-mass protostellar cores MNRAS 496, 3482-3501 (2020) (e.g. Svoboda et al 2019). This shows that the classification of sources as starless based on single-dish continuum observations (e.g.…”
Section: The Artémis Viewmentioning
confidence: 96%
See 3 more Smart Citations
“…Also, when observed with ALMA at high-angular resolution, singledish starless sources observed in high-mass star-forming regions systematically fragment into a set of low-mass protostellar cores MNRAS 496, 3482-3501 (2020) (e.g. Svoboda et al 2019). This shows that the classification of sources as starless based on single-dish continuum observations (e.g.…”
Section: The Artémis Viewmentioning
confidence: 96%
“…Also, nearly all high-angular resolution (≤1 ) observations of similar sources show sub-fragmentation (e.g. Louvet et al 2019;Sanhueza et al 2019;Svoboda et al 2019) casting doubts on the true physical meaning of the identified ArTéMiS compact sources. Our approach here is more generic: we compute the mass within the ArTéMiS beam solid angle at the location of the peak flux density of every identified leaf.…”
Section: Massesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at least the latter two examples are at comparably large distances of 3.4 and 4.9 kpc, respectively, reducing the ability to investigate structures at small physical spatial scales. Furthermore, recent investigations with the Atacama Large Millimeter Array (ALMA) and the Submillimeter Array (SMA) also started to further dissect samples of very young high-mass star-forming regions (e.g., Sanhueza et al 2019;Svoboda et al 2019;Li et al 2019Li et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%